Neuromechanical Consequences of Eccentric Load Reduction During the Performance of Weighted Jump Squats - Zhang, Q.; Zhang, L.; Yan, B.; Girard, O. (International Journal of Sports Physiology and Performance, 2023)
Purpose: To quantify the acute effects of a spectrum of eccentric load reductions on neuromechanical adjustments during the performance of weighted jump squats (WJSs).